Catechins and Caffeine Inhibit Fat Accumulation in Mice through the Improvement of Hepatic Lipid Metabolism - Chikako Sugiura; Shiho Nishimatsu; Tatsuya Moriyama; Sayaka Ozasa; Teruo Kawada; Kazutoshi Sayama (Journal of Obesity)
To elucidate the inhibiting mechanisms of fat accumulation by catechins, caffeine, and epigallocatechin gallate (EGCG), ICR mice were fed diets containing either 0.3% catechins or 0.1% EGCG and/or 0.05% caffeine for 4 weeks. After the feeding, intraperitoneal adipose tissues weights were significantly lower in the caffeine, catechins + caffeine, and EGCG + caffeine groups compared to controls. Hepatic fatty acid synthase (FAS) activity in the catechins + caffeine group was significantly lower, and the activities of acyl-CoA oxidase (ACO) and carnitine palmitoyltransferase-II (CPT-II) were significantly higher, compared to the control group. However, these activities were not observed in the other groups. FAS mRNA expression levels in the catechins + caffeine group were significantly lower than in the control group. ACO and CPT-II mRNA levels were not different among all of the treatment groups. These findings indicate that the inhibitory effects of fat accumulation via a combination of catechins, EGCG, or caffeine were stronger collectively than by either catechins, EGCG, or caffeine alone. Moreover, it was demonstrated that the combination of catechins and caffeine induced inhibition of fat accumulation by suppression of fatty acid synthesis and upregulation of the enzymatic activities involved in β-oxidation of fatty acid in the liver, but this result was not observed by combination of EGCG and caffeine.